Municipal finance and governance in Poland, the Slovak Republic, the Czech Republic, and Hungary - Chang Woon Nam; Rüdiger Parsche; Bettina Reichl (ifo Institut für Wirtschaftsforschung an der Universität München, 2001)
The recent process of political and economic transformation in eastern European countries has not only contributed to the decentralisation of political structure but also significantly enhanced the fiscal autonomy of municipalities belonging to these countries. Although the degree of self-governing ability of municipalities seems to vary from one country to another, many similar types of public activities have recently been assigned to local governments, and some taxes were also declared to be so-called local taxes. To be sure, this type of fiscal decentralisation has caused some additional problems, particularly for safeguarding the quality of publicly provided goods and services and for coordinating intergovernmental fiscal transfers between the central and local governments in an efficient way. For instance, some criticise that a large number of small-sized municipalities in the transition economies have suffered from financial bottleneck and have not been able to receive financial support from the central government that was necessary for their economic development. However, such a fiscal devolution trend appears to continue, in parallel to the ongoing democratisation and decentralisation. This study primarily deals with crucial issues surrounding the impact of national fiscal policy and the regulatory framework on local governments' expenditure behaviour and their ability to mobilise necessary revenues (i.e. tax income, grants and municipal borrowings) under the particular consideration of the institutional and administrative cooperation with the central government and of the (still existing) lesswell developed financial market in Poland, the Slovak Republic, the Czech Republic and Hungary.
Keywords: H20; H40; H60; H77; H80; 330; Polen; Slowakei; Tschechische Republik; Ungarn; Gemeindefinanzen; Kommunale Selbstverwaltung; Finanzbeziehungen; Finanzausgleich; Kommunalverschuldung; Vergleich; Polen; Slowakei; Tschechien; Ungarn